2007
DOI: 10.1189/jlb.0307158
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional profiling of human monocytes reveals complex changes in the expression pattern of inflammation-related genes in response to the annexin A1-derived peptide Ac1-25

Abstract: Annexin A1 is a glucocorticoid-regulated, anti-inflammatory protein, which plays an important role as an endogenous regulator of the inflammatory response. Many of these anti-inflammatory properties are retained in the N-terminal annexin A1 peptide Ac1-25, which is released from the full-length protein by a neutrophil elastase. To elucidate whether the anti-inflammatory activity of the bioactive peptide is solely a result of immediate post-translational effects, which include the shedding of L-selectin or also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 56 publications
0
14
2
Order By: Relevance
“…In order to achieve its biological effects, the protein is translocated from the cytosol to the cell surface where it binds to a G protein-coupled receptor belonging to the formyl peptide receptor family [23]. Glucocorticoids are known to induce both de novo synthesis and translocation of AnxA1 to the cell surface [6, 9–11] and there is consistent evidence that AnxA1 is a key mediator of anti-inflammatory actions in monocytes/macrophages [4, 5]. Although the effects of AnxA1 has been studied mainly in vitro using exogenous AnxA1, a previous in vivo gene expression profiling study of human PBMCs verified that AnxA1 was a candidate marker of inflammatory modulation [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to achieve its biological effects, the protein is translocated from the cytosol to the cell surface where it binds to a G protein-coupled receptor belonging to the formyl peptide receptor family [23]. Glucocorticoids are known to induce both de novo synthesis and translocation of AnxA1 to the cell surface [6, 9–11] and there is consistent evidence that AnxA1 is a key mediator of anti-inflammatory actions in monocytes/macrophages [4, 5]. Although the effects of AnxA1 has been studied mainly in vitro using exogenous AnxA1, a previous in vivo gene expression profiling study of human PBMCs verified that AnxA1 was a candidate marker of inflammatory modulation [24].…”
Section: Discussionmentioning
confidence: 99%
“…It is abundantly expressed in innate immune cells under normal conditions [2, 3]. In experimental models, AnxA1 or AnxA1-derived peptides exert a broad range of anti-inflammatory effects in monocytes, involving transcriptional changes as well as rapid post-translational effects [4, 5]. A number of studies have also shown that glucocorticoids induce de novo synthesis as well as translocation of AnxA1 to the cell surface in peripheral blood mononuclear cells (PBMCs) or isolated monocytes/macrophages [6–11].…”
Section: Introductionmentioning
confidence: 99%
“…38,39 However, downstream signaling after annexin A1 binding to its receptor involves rapid and transient activation of ERK1/2 and p38, which stays in strict contrast to the prolonged ERK-activation responsible for the antiapoptotic effect described in our study. 37,40 Moreover, only an N-terminal peptide of annexin A1 (Ac1-25) has been shown to activate all FPR receptors, binding of the physiologically relevant annexin A1 has been reported only for FPR2, which was not …”
Section: Pro-survival Action Of Glucocorticoids On Monocytes 451mentioning
confidence: 99%
“…Equal amounts of total cellular protein were analyzed by SDS-polyacrylamide gel electrophoresis (PAGE) and subsequent immunoblotting using rabbit polyclonal anti-EGF receptor antibody (sc-03; Santa Cruz Biotechnology). To investigate activation of the mitogen-activated protein (MAP) kinases ERK1/2, the membranes were probed with rabbit anti-phospho-ERK1/2 antibodies and subsequently stripped and reprobed for total ERK (mouse monoclonal phospho-p42/44 and rabbit polyclonal p42/44; Cell Signaling Technology, Danvers, MA) as described previously (Lange et al, 2007). Remaining EGFR levels after stimulation were analyzed by quantifying the intensities of the 180-kDa band representing the mature EGFR.…”
Section: Analysis Of Annexin A8 Rna Interference (Rnai) Egfr Degradamentioning
confidence: 99%